Evaluation of the composition and development of Maillard reaction in infant formulas - Nunes, Lauane (2018)
Infant formula has the function of replacing or complementing breast milk and its formulation is based on modified cow milk. Due to a large number of heat treatments, the formulas are subject to a series of reactions that cause a reduction in its quality, among them the Maillard reaction. In addition, it is important that these products provide sufficient quantities of all nutrients, therefore, a constant evaluation of the nutritional composition of products available in the market is necessary. Therefore, the objective of this work was evaluate the propagation of Maillard reaction in infant formulas and to investigate the centesimal composition of products under conditions of use over 60 days at 4 and 24 oC. It was observed a decrease in lactose, lysine content and pH; increase in moisture, HMF content, water activity and color difference. Possibly, lactose is associated with some proteins and amino acids, such as lysine, in the initial phases of Maillard reaction, and with the prolongation of the storage, there is production of intermediates such as HMF, formic acid, water, among others, in such a way that the intermediate compounds polymerize forming the pigments known as melanoidins. However by decreasing the storage temperature, it was observed a decrease in the Maillard reaction rates, and consequently, lower nutritional losses. Regarding the centesimal composition, almost all the infant formulas analyzed were within the limits established. In addition, they does not pose health risks to the infant in relation to the level of HMF. However, studies are still needed to clarify the effect of Maillard reaction on this type of product, what the real harm to the infant and review the micronutrient values.